Intestinal melatonin levels and gut microbiota homeostasis are independent of the pineal gland in pigs - Zheng, Jiaming; Zhou, Yewen; Zhang, Di; Ma, Kezhe; Gong, Yuneng; Luo, Xuan; Liu, Jiali; Cui, Sheng (Frontiers in Microbiology, 2024)
Introduction: Melatonin (MEL) is a critical neuroendocrine hormone primarily produced by the pineal gland. Pinealectomy (PINX) has been used as an endogenous MEL deficiency model to investigate the functions of pineal MEL and its relationship with various diseases. However, the effect of PINX on gastrointestinal tract (GIT) MEL levels and gut microbiome in pigs has not been previously reported. Methods: Using a new established pig PINX model, we detected the levels of MEL in the GIT by liquid chromatography-tandem mass spectrometry. In addition, we examined the effects of PINX on the expression of MEL synthesis enzymes, intestinal histomorphology, and intestinal barrier. Furthermore, 16S rRNA sequencing was performed to analyze the colonic microbiome. Results: PINX reduced serum MEL levels but did not affect GIT MEL levels. Conversely, MEL supplementation increased MEL levels in GIT and intestinal contents. Neither PINX nor MEL supplementation had any effect on weight gain, organ coefficient, serum biochemical indicators, or MEL synthetase Arylalkylamine N-acetyltransferase (AANAT) expression in the duodenum, ileum and colon. Furthermore, no significant differences were observed in intestinal morphology or intestinal mucosal barrier function among the treatments. Additionally, 16S rRNA sequencing revealed that PINX had no significant impact on the composition of the intestinal microbiota. Nevertheless, MEL supplementation decreased the abundance of Fibrobacterota and increased the abundance of Actinobacteriota, Desulfobacterota, and Chloroflexi. Conclusion: We demonstrated that MEL synthesis in the GIT is independent of the pineal gland. PINX had no influence on intestinal MEL level and microbiota composition in pigs, while exogenous MEL alters the structure of gut microbiota.